(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The Italian Constitutional Court, with its judgement no. 162/2014, has repealed the “unfair ban” on assisted reproduction with gamete donation established by law no. 40/2004. This paper analyses and comments on the way the law has been approved – through a harsh debate and an unsuccessful referendum – and how many judges tried to challenge it, asking for the intervention of the Constitutional Court. After the last judgement, how will assisted reproduction be regulated in Italy?